Establishment of Sorghum bicolor L. plants under different water regimes - Matos, Fabio Santos; Basílio, Amanda Ayda Garcia; Furtado, Brunno Nunes; Gratão, Mariana Souza; Borges, Larissa Pacheco; Amorim, Víctor Alves (Acta Iguazu, 2021)
The present study aim to evaluate the effect of water availability on initial growth of sorghum plants, also, identify the tolerance strategy to drought and excess of water. The study was carried out in a greenhouse covered with transparent plastic and shade cloth on the sides that intercept 50% of radiation at the State University of Goiás, Southeast Campus, Ipameri Unit. The Sorghum bicolor seeds were sown in 5 liters pots containing a mix of soil, sand and manure 3:1:1, respectively. The experimental design used was completely randomized, with six treatments and six replications. After 20 days of emergence, the plants was irrigated with water volumes according to 0%, 25%, 50%, 100%, 200% and 400% of daily evapotranspiration. The analysis was carried out 40 days after emergence (DAE). The water restriction limit growth of sorghum plants, however, to tolerate stress, the plants increase the root system and decrease the transpiration through the efficient stomatal control and maintain hydrated to support growth, besides that, decrease the concentration of leaf photosynthetic pigments as a photoprotection mechanism. The excess of water between 100% and 400% of evapotranspiration (ET) did not limit growth of Sorghum bicolor plants, because the high transpiration rate eliminated to atmosphere the excess of water, however, above 230% of ET, the plants showed smooth signs of decreased leaf initiation and water relative content.